2021
DOI: 10.1002/dvg.23407
|View full text |Cite
|
Sign up to set email alerts
|

The power of zebrafish models for understanding the co‐occurrence of craniofacial and limb disorders

Abstract: Summary Craniofacial and limb defects are two of the most common congenital anomalies in the general population. Interestingly, these defects are not mutually exclusive. Many patients with craniofacial phenotypes, such as orofacial clefting and craniosynostosis, also present with limb defects, including polydactyly, syndactyly, brachydactyly, or ectrodactyly. The gene regulatory networks governing craniofacial and limb development initially seem distinct from one another, and yet these birth defects frequently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 120 publications
0
12
0
Order By: Relevance
“…Because of its position, some have hypothesized that, like the clavicle in mammals, the cleithrum may be composed of both neural crest (NC) and mesodermal cells (Matsuoka et al, 2005). This could have important implications in human disease in that craniofacial and limb defects often co-occur, including in SHFM (reviewed in Gurrieri and Everman (2013); Truong and Artinger (2021)). Although there is currently no evidence that NC cells contribute to the cleithrum (Kague et al, 2012), NC cells have been labeled in gill pillar cells of zebrafish (Mongera et al, 2013) as well as the posterior gill arches of the little skate ( Leucoraja erinacea ) (Sleight & Gillis, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Because of its position, some have hypothesized that, like the clavicle in mammals, the cleithrum may be composed of both neural crest (NC) and mesodermal cells (Matsuoka et al, 2005). This could have important implications in human disease in that craniofacial and limb defects often co-occur, including in SHFM (reviewed in Gurrieri and Everman (2013); Truong and Artinger (2021)). Although there is currently no evidence that NC cells contribute to the cleithrum (Kague et al, 2012), NC cells have been labeled in gill pillar cells of zebrafish (Mongera et al, 2013) as well as the posterior gill arches of the little skate ( Leucoraja erinacea ) (Sleight & Gillis, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…While in vivo analysis of the behavior of key bone cells during bone remodeling in mice is invasive, by necessity depending on surgery and intravital imaging techniques [ 84 ], in fish osteoblasts and osteoclasts can be easily and non-invasively monitored in vivo using cell-specific reporter lines [ 85 ] ( Figure 3 A). Fish models are notable for understanding the craniofacial genetics [ 86 , 87 ], skeletal diseases, and even for the co-occurrence of craniofacial and limb disorders [ 88 ]. Contrary to mice studies, the development of the craniofacial skeleton, including the skull, can be observed in vivo and non-invasively, allowing researchers to investigate cellular behavior changes underpinning common craniofacial developmental conditions [ 89 ].…”
Section: Zebrafish As Animal Models To Accelerate Discoveries Of Huma...mentioning
confidence: 99%
“…Zebrafish develop a small number of bone structures within the first 5 days postfertilization (dpf; Figure 1a,b). The first arch forms the lower jaw (mandibular domain) and the palate (maxillary domain); the second arch forms the ceratohyal and hyomandibular bones, which connect the lower jaw to the neurocranium; and the third through the seventh arches give rise to the ceratobranchials, epibranchials, and pharyngobranchials (Kimmel, Miller, & Moens, 2001; Truong & Artinger, 2021). Then, cartilage cells are replaced by osteoblasts during the formation process.…”
Section: Craniofacial Structure Of Zebrafishmentioning
confidence: 99%